New teacher induction: Support that impacts beginning middle-level educators. Issue 1 (1st January 2016) - Martin, Kathryn L.; Buelow, Stephanie M.; Hoffman, Jennifer T.
Abstract: As teachers begin teaching, they are faced with many challenges. New teacher induction programs are common yet less than 1% of teachers actually receive what is considered a comprehensive induction where new teachers have opportunities to work with other colleagues in learning communities, observe experienced teachers' classrooms, be observed by expert mentors, analyze their own practice, and network with other novice teachers ([AAEA] 2004), Ingersoll & Smith, 2004). Most middle level educators are prepared for elementary or secondary education and lack the expertise to teach young adolescents, so guiding teachers in their early years is critical to their success. Elements of support that teachers perceived as beneficial included included mentoring with educators whom they had developed a relationship with and trusted. In addition to mentoring, professional development practices, such as common planning times and analysis of student work, helped new teachers continually develop. The teachers' experiences highlighted a need for a more structured system of support for beginning teachers and mentors who were specifically prepared and provided time to nurture new middle level teachers.